Makanan Sehat untuk Kesehatan Otak - Agnescia Clarissa Sera; Prisilia Oktaviyani (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2021)
Hard to focus and forgetful are learning problems often experienced by students. About dietary factors, skipping breakfast and eating unhealthy foods may cause the brain to work less optimally. Moreover, high-sodium foods that teenagers prefer can damage brain cells. If the pattern and selection of food in students are not immediately corrected, of course, this can interfere with their learning performance. For this reason, they need to know about the types of food and healthy eating patterns. Asrama Pendidikan Eka Sinta Palangka Raya was chosen to be the location for community service because its residents are students in junior and senior high school levels. Also, this location is not far from the Poltekkes Kemenkes Palangka Raya. Therefore, this institution will bring a real impact on the surrounding environment. This activity was carried out in November 2020, attended by 13 dormitory residents, four dormitory managers, and seven community service executors. In general, the activities run smoothly and bring new insights toward a good diet. Participants’ level of understanding was excellent (81.76%). The manager of Asrama Pendidikan Eka Sinta Palangka Raya wished this activity could be carried out sustainably by adding training materials, so that dormitory residents gain more skills, especially in processing functional food products to increase memory made from vegetable and fruit waste.